Timelines of science. (DK Publishing, 2022)
Packed with fascinating facts, amazing images, and some seriously staggering science, this science history book shows how thousands of years of human endeavor have expanded our knowledge and shaped our lives. Find out why the fruitless search for a potion of eternal life led to the birth to chemistry. See how the invention of magnifying lenses opened new windows into the cosmos and microcosmos. And learn how happy accidents led to the discovery of X-rays, batteries, pulsars, and even the big bang.